2010
DOI: 10.1007/s00213-010-1785-z
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating scopolamine-induced disrupted and persistent latent inhibition: stage-dependent effects of glycine and physostigmine

Abstract: These results extend the pharmacological differentiation between scopolamine-induced disrupted and persistent LI and indicate that the scopolamine LI model may have a unique capacity to discriminate between typical APDs, atypical APDs, and cognitive enhancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
1
1
0
Order By: Relevance
“…We administered DCS prior to CS pre-exposure and observed no effect on latent inhibition. Consistent with this finding, the modulation of NMDA receptor function by glycine (administered prior to both preexposure and conditioning) also does not affect latent inhibition (Barak and Weiner 2010). However, DCS given at conditioning may have had a different effect on the expression of latent inhibition.…”
Section: Discussionsupporting
confidence: 59%
“…We administered DCS prior to CS pre-exposure and observed no effect on latent inhibition. Consistent with this finding, the modulation of NMDA receptor function by glycine (administered prior to both preexposure and conditioning) also does not affect latent inhibition (Barak and Weiner 2010). However, DCS given at conditioning may have had a different effect on the expression of latent inhibition.…”
Section: Discussionsupporting
confidence: 59%
“…275,276 LSD and psilocybin mushrooms are also consistently ranked by drugabuse experts as much less harmful to the individual user or to society than alcohol. 277,278,279,280 No Long-Term Sequelae A number of recent studies have found no long-term negative effects of LSD or other classical hallucinogen (psilocybin, DMT, & mescaline) exposure.…”
Section: Lysergic Acid Diethylamide (Lsd) Psilocybin Dmt and Mescamentioning
confidence: 99%